Comparative hologenomics of two Ixodes scapularis tick populations in New Jersey - Dana C. Price; Julia R. Brennan; Nicole E. Wagner; Andrea M. Egizi (PeerJ, 2021)
Tick-borne diseases, such as those transmitted by the blacklegged tick Ixodes scapularis, are a significant and growing public health problem in the US. There is mounting evidence that co-occurring non-pathogenic microbes can also impact tick-borne disease transmission. Shotgun metagenome sequencing enables sampling of the complete tick hologenome—the collective genomes of the tick and all of the microbial species contained therein, whether pathogenic, commensal or symbiotic. This approach simultaneously uncovers taxonomic composition and allows the detection of intraspecific genetic variation, making it a useful tool to compare spatial differences across tick populations. We evaluated this approach by comparing hologenome data from two tick samples (N = 6 ticks per location) collected at a relatively fine spatial scale, approximately 23 km apart, within a single US county. Several intriguing variants in the data between the two sites were detected, including polymorphisms in both in the tick’s own mitochondrial DNA and that of a rickettsial endosymbiont. The two samples were broadly similar in terms of the microbial species present, including multiple known tick-borne pathogens (Borrelia burgdorferi, Babesia microti, and Anaplasma phagocytophilum), filarial nematodes, and Wolbachia and Babesia species. We assembled the complete genome of the rickettsial endosymbiont (most likely Rickettsia buchneri) from both populations. Our results provide further evidence for the use of shotgun metagenome sequencing as a tool to compare tick hologenomes and differentiate tick populations across localized spatial scales.